Correlating Coefficient of Friction and Shear Force to Platen Motor Current in Tungsten and Interlayer Dielectric Chemical Mechanical Planarization at Highly Non-Steady-State Conditions. (16th October 2019) - Headley, R.; Frank, C.; Sampurno, Y.; Philipossian, A.
Abstract : Correlations between shear force and platen motor current (PMC), as well as those between coefficient of friction (COF) and PMC were investigated for various tungsten and interlayer dielectric (ILD) chemical mechanical planarization (CMP) cases where the processes were highly non steady-state. We chose to initially focus on non-steady-state conditions because we believed the relationships among shear force, COF and platen motor current to be clearer as opposed to steady-state conditions. Shear force, normal force and PMC data were collected from twelve different Stribeck+ curves at an acquisition frequency of 1, 000 Hz and analyzed in order to determine any emerging trends. For the 12 cases, involving 8 pre-polished blanket CVD tungsten and 4 silicon dioxide blanket wafers, it was discovered that PMC closely mirrored shear force as evidenced by a high average correlation coefficient (0.955) and coefficient of determination (0.916) obtained from all runs. For COF vs. PMC, the average correlation coefficient and coefficient of determination for all cases were 0.758 and 0.608, respectively. These average values were dragged down by 5 cases in which the dominant tribological mechanism was found to be "boundary lubrication" where COF changed minimally with pseudo-Sommerfeld number.